Back Cover: Ultrasmall Palladium Nanoclusters as Effective Catalyst for Oxygen Reduction Reaction (ChemElectroChem 8/2016). Issue 8 (13th July 2016) - Zhao, Shuo; Zhang, Hui; House, Stephen D.; Jin, Renxi; Yang, Judith C.; Jin, Rongchao
Abstract : The Back Cover picture highlights a one‐pot synthesis of ultrasmall thiolate‐protected palladium nanoclusters, which can serve as efficient and durable electrocatalysts for oxygen reduction reactions. More information can be found in the Full Paper by S. Zhao et al. onpage 1225 in Issue 8, 2016 (DOI:10.1002/celc.201600053 ).